1996
DOI: 10.1056/nejm199603073341003
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide for High-Altitude Pulmonary Edema

Abstract: The inhalation of nitric oxide improves arterial oxygenation in high-altitude pulmonary edema, and this beneficial effect may be related to its favorable action on the distribution of blood flow in the lungs. A defect in nitric nitric oxide synthesis may contribute to high-altitude pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
189
3
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 291 publications
(200 citation statements)
references
References 24 publications
3
189
3
4
Order By: Relevance
“…The initial impetus for the study was the inverse relation between pulmonary NO and pulmonary arterial pressure found in animal and human experiments (6,7,9,14,15,22,23,27,28). That relation was not found in this study, despite adequate statistical power.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The initial impetus for the study was the inverse relation between pulmonary NO and pulmonary arterial pressure found in animal and human experiments (6,7,9,14,15,22,23,27,28). That relation was not found in this study, despite adequate statistical power.…”
Section: Discussionmentioning
confidence: 60%
“…1) Exhaled NO does not increase after experimental elevation of cardiac output (12). 2) Exhaled NO is decreased on acute exposure to high altitude, despite elevation of cardiac output (11,23,30). 3) Experimental inhibition of NO synthesis causes a decrease in cardiac index at sea level (6,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons who are prone to the condition have higher PAP at rest and in response to hypoxia, altitude and exercise than those who are resistant to it. Inhalation of nitric oxide is reported to be beneficial in subjects prone to HAPO by reducing PAP [17]. Oelz [IS] and Bartsch [191 have demonstrated protective and therapeutic effects of lowering PAP with nifedipine without impairing performance in climbers prone to HAPO.…”
Section: Discussionmentioning
confidence: 99%
“…24 Color Doppler echocardiography was used to locate the tricuspid-regurgitation jet. The maximal velocity was then determined by careful application of the continuous-wave sampler on the regurgitation jet.…”
Section: Echocardiographymentioning
confidence: 99%